α-Bisabolol alleviates diesel exhaust particle-induced lung injury and mitochondrial dysfunction by regulating inflammatory, oxidative stress, and apoptotic biomarkers through the c-Jun N-terminal kinase signaling pathway - Sumaya Beegam; Nur Elena Zaaba; Ozaz Elzaki; Abderrahim Nemmar (Frontiers in Pharmacology)
IntroductionExposure to particulate matter ≤2.5 μm in diameter (PM2.5) is associated with adverse respiratory outcomes, including alterations to lung morphology and function. These associations were reported even at concentrations lower than the current annual limit of PM2.5. Inhalation of PM2.5, of which diesel exhaust particles (DEPs) is a major component, induces lung inflammation and oxidative stress. α-Bisabolol (BIS) is a bioactive dietary phytochemical with various pharmacological properties, including anti-inflammatory and antioxidant actions. Here, we evaluated the possible protective effects of BIS on DEP-induced lung injury.MethodsMice were exposed to DEPs (20 µg/mouse) or saline (control) by intratracheal instillation. BIS was administered orally at two doses (25 and 50 mg/kg) approximately 1 h before DEP exposure. Twenty-four hours after DEP administration, multiple respiratory endpoints were evaluated.ResultsBIS administration was observed to prevent DEP-induced airway hyperreactivity to methacholine; influx of macrophages, neutrophils, and lymphocytes in the bronchoalveolar lavage fluid; and increases in epithelial and endothelial permeabilities. DEP exposure caused increases in the levels of myeloperoxidase, proinflammatory cytokines, and oxidative stress markers in lung tissue homogenates, and all these effects were abated by BIS treatment. The activities of mitochondrial complexes I, II, III, and IV were markedly increased in the lungs of mice exposed to DEPs, and these effects were significantly reduced in the BIS-treated group. Intratracheal instillation of DEPs induced DNA damage and increase in the apoptotic marker cleaved caspase-3. The latter effects were prevented in mice treated with BIS and exposed to DEPs. Moreover, BIS mitigated DEP-induced increase in the expression of phospho-c-Jun N-terminal kinase (JNK) in a dose-dependent manner.DiscussionBIS markedly alleviated DEP-induced lung injury by regulating the inflammatory, oxidative stress, and apoptotic biomarkers through the JNK signaling pathway. Following additional studies, BIS may be considered as a plausible protective agent against inhaled-particle-induced pulmonary adverse effects.